A cisticercose e o prejuízo ao produtor - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
Bovine cysticercosis is a parasitic disease caused by the infection of cattle with the larvae of Taenia saginata, a species of tapeworm. Cattle contract the infection by ingesting food or water contaminated with Taenia saginata eggs, which are shed in the feces of infected humans. When eggs are ingested by cattle, they develop into larvae that can migrate to the animal's muscles and form cysts, resulting in cysticercosis. These cysts can be found mainly. The presence of cysticerci in the muscle tissues of cattle is a public health concern, as humans can acquire the infection by consuming undercooked or undercooked beef containing cysticerci. However, unlike human cysticercosis caused by Taenia solium, bovine cysticercosis does not lead to the formation of cysticerci in the human central nervous system. Controlling bovine cysticercosis involves preventive measures, such as careful inspection of animals slaughtered in slaughterhouses and educating consumers about the risks of consuming raw or undercooked beef. In addition, proper hygiene practices in meat production and animal handling are also key to reducing the risk of transmitting the disease to humans.
Cysticercosis and losses to producers
Keywords: Abate; Bovinos; Cisticercose; Produção animal; Slaughter; Cattle; Cysticercosis; Animal production; CIENCIAS AGRARIAS